OPTIMIZING PATIENT CARE AND ADMINISTRATIVE EFFICIENCY: THE INTEGRAL ROLES OF MEDICAL SECRETARIES, DENTAL ASSISTANTS, AND HEALTH ADMINISTRATORS IN HEALTHCARE SETTINGS - Khalid Obaid Zaram Alanazi, Sauod Hamoud Al Harbi, Saleh Mulhi Alharbi, Dhaifallah Hadi Alenazi,; Saad Fraih Hamed Alanazi, Naif Humaian Alrasheedi, Hamad Ghathith Alanazi, (Chelonian Research Foundation, 2022)
Medical secretaries, dental assistants, and health administrators fulfill essential complementary roles supporting high quality patient care and optimal administrative functioning in healthcare organizations. However, the nature and value of their work are often underrecognized. This paper synthesizes literature on the multifaceted responsibilities, specialized competencies, and impacts of these roles on patients, providers, and health systems. Findings underscore that medical secretaries enable efficient clinic operations, dental assistants expand dental teams’ capabilities, and health administrators develop organizational strategy and capabilities. Despite challenges like high demands, inadequate staffing, and complex technologies, those in these roles have a vital impact through facilitating effective behind-the-scenes communication, coordination, documentation, financing, infrastructure, analytics, and more. Fostering collaborative team practice and acknowledging the contributions of these professionals are imperative for delivering comprehensive patient-centered care.